2018
DOI: 10.1097/scs.0000000000004460
|View full text |Cite
|
Sign up to set email alerts
|

Office-Based Three-Dimensional Printing Workflow for Craniomaxillofacial Fracture Repair

Abstract: Three-dimensional printing of patient-specific models is being used in various aspects of craniomaxillofacial reconstruction. Printing is typically outsourced to off-site vendors, with the main disadvantages being increased costs and time for production. Office-based 3-dimensional printing has been proposed as a means to reduce costs and delays, but remains largely underused because of the perception among surgeons that it is futuristic, highly technical, and prohibitively expensive. The goal of this report is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 21 publications
0
21
0
Order By: Relevance
“…65 The ability of 3D planning has the potential to not only reduce OR time and costs, but also aid in educating trainees in understanding the principles of fracture management. [66][67][68][69][70] King et al showed that the use of 3D printers for fabrication of models to prebend plates drastically reduced operating time and costs (►Fig. 15).…”
Section: Three-dimensional Printingmentioning
confidence: 99%
“…65 The ability of 3D planning has the potential to not only reduce OR time and costs, but also aid in educating trainees in understanding the principles of fracture management. [66][67][68][69][70] King et al showed that the use of 3D printers for fabrication of models to prebend plates drastically reduced operating time and costs (►Fig. 15).…”
Section: Three-dimensional Printingmentioning
confidence: 99%
“…That is, a mirror image of a non-injured facial skeleton serves as an excellent template to build upon. It was not until recently, however, that studies started to emerge demonstrating the use of CAD/CAM principles with custom milled and/or pre-bent plates for mandibular or complex facial trauma [14,[20][21][22][23][24] . Currently, these investigations generally follow two distinct paths.…”
Section: Off-site Cad/cam Vs Point-of-care 3d Printingmentioning
confidence: 99%
“…Several studies have described a less expensive alternative using on-site commercially available 3-dimensional (3D) printers. 10,11 This method requires the fabrication of 3-dimensionally printed models from in-office printers and either preoperative 11 or intraoperative 10 plate bending. A study showed that preoperative plate bending has the added benefit of decreasing OR time and consequently costs 11 ; however, this study required manual post-fabrication manipulation to anatomically reduce the fracture.…”
mentioning
confidence: 99%
“…A study showed that preoperative plate bending has the added benefit of decreasing OR time and consequently costs 11 ; however, this study required manual post-fabrication manipulation to anatomically reduce the fracture. Elegbede et al 10 described an in-office method to virtually reduce simple mandible fractures based on mirror imaging of the contralateral side but contouring of the reconstruction plate to the model was performed intraoperatively, negating the cost savings of preoperative plate adaptation. It is important to note that 3D Slicer was used in this study, which is currently not approved by the US Food and Drug Administration (FDA) for patient use in the United States.…”
mentioning
confidence: 99%